Record of Platynota rostrana (Walker, 1863) (Lepidoptera: Tortricidae) in citrus from Mexico. - Varela-Fuentes, S.; Brown, J. W.; Silva-Aguirre, G. (Instituto de Ecología, A.C., 2009)
Platynota rostrana is recorded for the first time as citrus pests in Mexico, on Citrus sinensis and Citrus limon.